1995
DOI: 10.21273/hortsci.30.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Lightly Processed Fruits and Vegetables

Abstract: 1989). Wound ethylene production is usually greater in preclimacteric and climacteric than postclimacteric tissues (Abeles et al., 1992), and whereas wound ethylene has no effect on ripening of nonclimacteric fruit, it may advance ripening of climacteric fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
0
92

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(252 citation statements)
references
References 28 publications
4
156
0
92
Order By: Relevance
“…Bolin, Stafford, King, and Huxsoll (1977) reported that chlorine dips produced similar results to sulphur dioxide in reducing browning of shredded lettuce. Inclusion of 175 ppm NaOCl in the rinse water significantly reduced the browning of snap beans (Brecht, 1995), while 17.5 ppm hypochlorite solution inhibited browning of sliced apples and potatoes (Brecht et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Bolin, Stafford, King, and Huxsoll (1977) reported that chlorine dips produced similar results to sulphur dioxide in reducing browning of shredded lettuce. Inclusion of 175 ppm NaOCl in the rinse water significantly reduced the browning of snap beans (Brecht, 1995), while 17.5 ppm hypochlorite solution inhibited browning of sliced apples and potatoes (Brecht et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Fresh-cut operation induces wound ethylene production. Wound ethylene can accelerate ripeness and senescence of fruits and vegetable (Brecht, 1995), and can also induce synthesis of some enzymes involved in browning reactions or substrate biosynthesis (Rolle & Chism, 1987). Fig.…”
Section: The Respiration Rate and Ethylene Productionmentioning
confidence: 99%
“…The wounding of plant tissues induces elevated respiration and ethylene production, enzymatic browning, membrane lipid degradation, production of secondary metabolites, and water loss (Watada, Abe, & Yamauchi, 1990). Minimising the consequences of wounding in fresh-cut products will help in increasing their shelf-life (Brecht, 1995). Therefore, combined technologies of chemical and physical treatments, packaging, and control of temperature and atmosphere have been commercially used for preparing various fresh-cut fruits and vegetables (Rico, Martin-Diana, Barat, & Barry-Ryan, 2007;Soliva-Fortuny & Martin-Belloso, 2003).…”
Section: Introductionmentioning
confidence: 99%